Predict the Possibility of Esophageal Varices in HCV Patients on the Basis of Fibro Scan Scoring System (Medical Forum Monthly, 2024)
Objective: To predict the possibility of Esophageal varices in HCV patients on the basis of fibro scan scoring system.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at Mamji Hospital from September 2013 to August 2014.Materials and Methods: Total 87 patients with chronic liver disease with HCV were enrolled. They were evaluated for the treatment of chronic viral hepatitis C. The study was conducted in a private Hospital of F.B. area Karachi. The consent were taken and record was gathered on a preset proforma. All patient had done with abdominal ultrasound, fibro scan and upper endoscopy and laboratory investigation. All the fibro scan was done by single department and all the upper endoscopies were performed by same gastroenterologist. The data was analysed on SPSS version 15.Results: All the patients were undergone fibro scan and divided into two groups according to their score offibro scan of 8Kpa into group I with low score and group II with high score. All patients under went upper endoscopy and the result were also divided into two groups those who had varices and those who had not.Total 87 patients. Males were 55 and females were 32. The fibro scan scoring was divides into two group. Group I was less than 8Kpa and group II was more than 8 Kpa. Among this 57 were in group I and 30 were in group II. The upper endoscopy result was also divided into two groups and in group I there were only one cases of early varices while 28 patients were show esophageal varices in group II.Conclusion: It is concluded that fibro scan is a good non-invasive measure to predict probable esophagealvarices.